Prevalence and patterns of antiretroviral resistance in HIV-infected Latin American asylum seekers - Samuel Manzano; Juan Torres-Macho; Neda Deihim-Rahampour; Guillermo Cuevas; Felipe Perez-Garcia; Luz Balsalobre; Salvador Resino; Matilde Sanchez-Conde; Jorge Valencia; Pablo Ryan (Scientific Reports)
Abstract The recent increase in Latin American asylum seekers in Spain has been accompanied by a rise in HIV diagnoses. However, their clinical profile, particularly regarding antiretroviral resistance, is poorly characterized. We aimed to assess the prevalence of resistance-associated mutations and their impact on treatment management in this vulnerable population. We conducted a prospective cohort study (2022–2023) with six-month follow-up, enrolling Latin American asylum seekers living with HIV, attending their first HIV consultation in Spain. Individuals with a viral load > 1,000 copies/mL, regardless of prior ART exposure, underwent genotypic resistance testing. Mutations were identified using the WHO Surveillance Drug Resistance Mutations (SDRM) list, and resistance was interpreted via the Stanford HIV Drug Resistance Database algorithm. Of 653 participants, 153 met inclusion criteria, and 141 (21.6%) had valid resistance results. Overall, 22.7% harbored SDRMs to NNRTIs, NRTIs, or PIs (15.0% ART-naïve vs. 32.8% ART-experienced). NNRTI mutations were most frequent (21.3%), particularly in ART-experienced individuals (31.1%). NRTI mutations were present in 7.1% overall (13.1% ART-experienced). The most common mutations were K103N/S (19.1%), P225H (5.0%), and M184V (4.3%). Among ART-experienced individuals, resistance to efavirenz, nevirapine, and rilpivirine was 31.1%, 32.7%, and 19.7%, respectively; 11.4% showed lamivudine resistance. Notably, 82.3% of ART-experienced participants reported barriers to healthcare access, with a 90% rate of treatment discontinuation. In this cohort of Latin American asylum seekers, resistance to NNRTIs was alarmingly high, especially among those with prior ART exposure and interrupted treatment. These findings underscore the need for optimized treatment strategies and improved healthcare access for migrant populations with HIV.